KAPASITAS ASIMILASI BEBAN PENCEMARAN DI PERAIRAN TELUK RIAU - Idris, Fadhliyah; Koenawan, Chandra Joei; Jumsurizal, Jumsurizal; Syakti, Agung Dhamar (Pusat Penelitian Sumberdaya Pesisir dan Laut, Universitas Maritim Raja Ali Haji, Indonesia, 2018)
Riau bay, Tanjungpinang City has been subject for domestic wastes contamination due to the high number of population living in the coastal area. This study aims to determine water quality condition including the pollutant load and the level of assimilation capacity in Riau bay waters. Using a survey method by purposive sampling strategy, the research was conducted by analyzing several physic-chemicals parameters. The results showed the measured physical parameters was still below the threshold level stipulating Minister Decree No. No 51 of 2004. Pollutant loads represented by BOD5, TSS and ammonia were 12,71 mg/L, 239,95 mg/L and 5,33 mg/L respectiely. Our finding showed the assimilation capacity level for BOD5, TSS and ammonia were 159,26 ton/year, 530,98 ton/year and 0,86 ton/year, respectively.